21th century physics learning in senior high school through interactive computer simulation to enhance students achievement - A Swandi; B D Amin; F Muin (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
This study aims to harness interactive computer simulation on physics concept that have been developed to improve students achievement by determining the differences in physics learning outcomes of students who were taught using computer simulations with students who were taught using conventional media and also evaluating students activity and their perception. The research type is true experiment with Posttest-Only Control Design. The research instrument used is the test of physics learning result of 20 questions in the form of multiple choice test which has valid on "Fluid" subject. Data analysis techniques used in this study is descriptive statistics and hypothesis testing. The results of descriptive analysis showed that the average score of physics learning outcomes of learners who were taught using a computer simulation is 13.5 and the average score of physics learning outcomes of learners who were taught using conventional media is 10. The results of hypothesis testing showed that there are significant difference in physics learning outcomes between learners who were taught using computer simulations with learners who were taught using conventional media. The percentage of students activity and their perception are above 85% that indicate students were active and agree on physics learning through interactive computer simulation